Different routes of insulin administration do not influence serum free thiols in type 1 diabetes mellitus. Issue 4 (8th August 2019) - van Dijk, Peter R.; Waanders, Femke; Logtenberg, Susan J. J.; Groenier, Klaas H.; Vriesendorp, Titia M.; Kleefstra, Nanne; van Goor, Harry; Bilo, Henk J. G.
Abstract: Aims: Intraperitoneal (IP) insulin administration is a last‐resort treatment option for selected patients with type 1 diabetes mellitus (T1DM). As the IP route of insulin administration mimics the physiology more closely than the subcutaneous (SC) route, we hypothesized that IP insulin would result in less oxidative stress (expressed as systemic level of free sulphydryl (R‐SH) content) compared to SC insulin in subjects with T1DM. Materials and methods: Prospective, observational case‐control study. Serum thiol measurements were performed at baseline and at 26 weeks in age‐ and gender‐matched patients with T1DM. Serum‐free thiols, compounds with a R‐SH group that are readily oxidized by reactive oxygen species, are considered to be a marker of systemic redox status. Results: A total of 176 patients, 39 of which used IP and 141 SC insulin therapy were analysed. Mean baseline R‐SH concentration was 248 (31) μmol/L. In multivariable analysis, the route of insulin therapy had no impact on baseline R‐SH levels. The estimated geometric mean concentrations of R‐SH did not differ significantly between both groups: 264 (95% CI 257, 270) for the IP group and 258 (95% CI 254, 261) for the SC group with a difference of 6 (95% CI −2, 14) μmol/L. Conclusions: Based on R‐SH as a marker of systemic oxidative stress, these findings demonstrate that the route of insulin administration, IP or SC, does not influence systemic redox status in patients with T1DM.